PENERAPAN ALGORITMA CERTAINTY FACTOR DAN PEMODELAN UML DALAM MERANCANG APLIKASI DIAGNOSIS PENYAKIT GASTRITIS - Andreas Nugraha Putra; Setiaji; Ishak, Riswandi; Hudin, Jamal Maulana (LPPM STMIK ANTAR BANGSA, 2021)
Abstract-Implementation Centainty Factor Algorthm and UML modelling in designing the application of the diagnosis of Gastritis disease. Ignorance of gastritis disease and the limitation of handling the disease is often experienced by teenagers. Therefore we need for action / treatment quickly to prevent gastritis disease. Gastritis is an inflammatory process in the mucosal layer and gastric submucosa as a mechanism of mucosal protection when there is accumulation of bacteria or other irritant substances. The inflammatory process may be mild (Dyspepsia), moderate (Gerd) and acute Gastritis. Expert system requires a method or rule in solving the problem of gastritis disease is by certainty factor method. The method certainty factor (CF) can defined the size of certainty by the fac or rulest, to describe the level of expert confidence to the problem at hand. Therefore in this study developed expert system that can be accessed through mobile devices such as android phone. The delivery of information was done using a mobile device, so it can be concluded that the research is implemented into the android application. So with the manufacture of expert systems to diagnose gastritis disease can help people, especially in adolescence to know the problems and severity such as mild, chronic gastritis symptoms. Keywords-Expert System, Certainty Factor, Diagnosis of Gastritis Disease Referensi : [1] IDI, â€œPanduan Praktik Klinis Bagi Dokter di Fasilitas Pelayanan Kesehatan Primer,â€ Menteri Kesehatan Republik Indonesia., pp. 162, 364, 2017. [2] D. Wahyu, Supono, and N. Hidayah, â€œPola Makan Sehari-hari Penderita Gastritis,â€ J. Inf. Kesehat. Indones., vol. 1, no. 77, pp. 17â€“ 24, 2015. [3] N. A. Ritonga, â€œSISTEM PAKAR MENDIAGNOSA PENYAKIT LAMBUNG,â€ Pelita Inform. Budi Darma, vol. V, no. November, pp. 157â€“161, 2013. [4] H. T. Sihotang, â€œSistem pakar untuk mendiagnosa penyakit pada tanaman jagung dengan metode bayes,â€ vol. 3, no. 1, 2018. [5] B. Susetyo, I. Nurhayati, I. Purnahayu, and P. Eosina, â€œModel Evaluasi Kinerja SDM Geospasial Menggunakan Metode CPI dan CPD Berbasis WebGIS,â€ vol. 2020, 2017. [6] F. Akbar, S.setiaji, R. Ishak, D. Saputra, and B. Masruri, â€œRancang Bangun Sistem Informasi Karang Taruna Menggunakan Metode Waterfall,â€ Khatulistiwa Inform., vol. VIII, no. 1, pp. 7â€“12, 2020,[Online]. Available: www.bsi.ac.id. [7] N. Sari and B. Sembiring, â€œBAKTERI SALMONELLA DALAM TUBUH MANUSIA MENGGUNAKAN METODE CERTAINTY FACTOR,â€ pp. 394â€“399, 2014. [8] M. Zunaidi, M. Rasyid, and I. Zulkarnain, â€œPenerapan Metode Certainty Factor dalam Teknik Photography untuk Menentukan Settingan Kamera DSLR yang Menghasilkan Gambar Terbaik,â€ J. Ilm. Saintikom, vol. 14, p. 186, 2015. [9] J. A. Widians and A. Utomo, â€œSISTEM PAKAR DIAGNOSA DYSPEPSIA DENGAN CERTAINTY FACTOR,â€ pp. 6â€“8, 2015. [10] H. A. Hidayat and G. Gumilang, â€œSistem Pakar Diagnosis Penyakit Yang Disebabkan Oleh Rokok Dengan Metode Forward Chaining,â€ Jutekin, vol. 3, no. 1, pp. 27â€“36, 2017.